Development of a Learning Ecosystem Using Digital Knowledge Engineering Through MOOCs Knowledge Repository System - Thanachawengsakul, Nattaphol; Wannapiroon, Panita (International Journal of Engineering Pedagogy (iJEP), 2021)
This paper presents the development of a learning ecosystem using digital knowledge engineering through a MOOCs knowledge repository system. This system comprises four parts: (1) Stakeholders, including instructors and learners; (2) A digital knowledge engineering learning process that describes the roles of instructors and learners, learning activities, and instructional tools; (3) A MOOCs knowledge repository system, which is the software de-veloped to enhance digital entrepreneurs’ competencies; and (4) Digital entrepreneurs’ competencies, which describe learning outcomes using the digital knowledge engineering learning process. The suitability of the learning ecosystem was assessed by twelve experts possessing at least three years of related experience. They judged its suitability to be at the highest level. This study can be used to support further development of the MOOCs knowledge repository system assess digital entrepreneurs’ competencies according to digital knowledge engineering learning process.